Effective Laws to End HIV and AIDS: Next Steps for Parliaments - IPU, UNDP (2012)
This publication draws on a growing body of international evidence to inform parliamentarians about the types of laws that are helpful and unhelpful in the AIDS response. There is a focus on “key populations” since these are often the target of legislation: however, many of the lessons apply to any legislation that impacts on HIV. Such lessons may be useful for legislators who wish to review their existing laws, avoid passing unhelpful laws or put into motion new, positive legislation.